The 3D-Language Acquisition Test and the Hard-of-Hearing - Usha K.R (Journal of All India Institute of Speech and Hearing, 1970)
A brief summary of the present study and the conclusions drawn are given below : A group of twenty-eight young, hard-ofhearing children in the age range of 18months to 36 months were studied for their performance on the "3D-Language Acquisition Test". Six age groups, with an interval of three months between each,were considered within the age range mentioned above.